Exosomal miR-432-5p, miR-4433b-5p, and miR-599: Biomarkers for Monitoring the Severity of Anti-N-methyl-D-aspartate Receptor Encephalitis - Zhuxiao Xie; Lei Liu; Yanjun Guo; Hanqiu Jiang; Lin Li; Zhixin Qiao; Jiawei Wang (Journal of Integrative Neuroscience)
Background: Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a rare disease with a high disability rate, characterized by acute-to-subacute psychiatric and/or neurological symptoms. Continuous intrathecal antibody synthesis does not correlate with the active phase of encephalitis and antibody titers do not directly reflect the severity of the condition. Currently, there is a lack of biomarkers for disease monitoring. This study focuses on finding novel peripheral blood biomarkers that can accurately monitor the severity of anti-NMDAR encephalitis. Methods: Peripheral blood samples were collected from patients with anti-NMDAR encephalitis, including those with acute-phase (autoimmune encephalitis (AE)-a group) and stable-phase (AE-s group) autoimmune encephalitis. Healthy individuals were included as controls (HC group). We isolated exosomal microRNAs (miRNAs) from the samples and screened differentially expressed miRNAs through next-generation sequencing. The sequencing results were validated using quantitative real-time qPCR (RT-qPCR). Furthermore, we conducted a correlation analysis between the expression levels of the screened miRNAs and clinical severity. Finally, we performed functional pathway analysis to explore the underlying mechanisms in anti-NMDAR encephalitis. Results: We found that exosomal miR-432-5p, miR-4433b-5p, and miR-599 exhibited significant differences between patients with anti-NMDAR encephalitis and healthy controls, as well as at various phases of the disease. The expression of miR-432-5p and miR-4433b-5p were negatively correlated with clinical severity. We further identified that key pathways including rhythmic processes and glutamatergic signaling play significant roles in the pathogenesis of anti-NMDAR encephalitis. Conclusions: Our research indicated that exosomal miR-432-5p, miR-4433b-5p, and miR-599 were correlated with the severity of anti-NMDAR encephalitis and can serve as potential biomarkers for disease monitoring. Moreover, the key functional pathways predicted by these miRNAs may play crucial roles in disease progression.